LEVEL 1 CALIBRATION OF HDM-4 ANALYSIS WITH A CASE STUDY (Malaysian Journal of Civil Engineering, 2018)
Adequate budget allocation would require the HDM-4 model to generate good prediction of the actual pavement deterioration behavior. The need for a calibration of the HDM model to local condition is therefore an essential component of the pavement management process. Reliable calibration factors are useful for budgeting purpose and it avoids under estimate or over estimates the budget. This paper presents a case study where a level 1 calibration has been carried out for a State Highway in Uttar Pradesh, India. The climatic condition of the site is under humid, hot and high monthly precipitation throughout the year. Two methods have been proposed to find out the calibration factors. The calibration factors namely roughness age environment, crack initiation and crack propagation are found to be 0.650, 0.970 and 1.030 respectively for the case study using method 1 calibration method and 0.650, 0.864 and 1.157 respectively using method 2 calibration. Economic analysis has been carried out taking default calibration factors and level 1 calibration factors and NPV (net present value) and IRR (internal rate of return) were found Rs. (million) 368.1 (26.5 %) and 422.4 (27.9 %) respectively. Level 1 Calibration involved desk study and many default values have been adopted but the major factors like roughness age environment, crack initiation and crack propagation are important to simulate local condition. A well calibrated model for this local condition would reduce the possibility of future funding shortages. Level 1 calibration may be carried out easily based on few secondary data within few weeks and useful for economic analysis, prioritization and budgeting for maintenance of the road network.